Introduction Introdução/Introduction - José Roberto O’Shea (Ilha do Desterro, 2008)
To facilitate study, the literature that has been produced in the
territory which comprises today the South of the United States is often divided roughly into five periods: Literature of the Colonial South; Literature of the Old South (i.e., Antebellum); Postbellum Literature; the Southern Literary Renascence; and Literature After the Renascence. The division also points to the fact that "Southern Literature" can be seen to go back to the days of the colonies. The
reader of the present issue of Ilha do Desterro, entitled Literature of the South of the United States, will readily notice, however, that all articles deal with twentieth-century writings and authors. Initially, as guest editor, I intended to publish articles on earlier periods as well, since, as Louis Rubin and others have shown, the earlier literature
contributes in concrete and fascinating ways to the development of the literary imagination and intelligence that would flower in the twentieth-century Southern Literary Renascence and later. To facilitate study, the literature that has been produced in the
territory which comprises today the South of the United States is often divided roughly into five periods: Literature of the Colonial South; Literature of the Old South (i.e., Antebellum); Postbellum Literature; the Southern Literary Renascence; and Literature After the Renascence. The division also points to the fact that "Southern Literature" can be seen to go back to the days of the colonies. The
reader of the present issue of Ilha do Desterro, entitled Literature of the South of the United States, will readily notice, however, that all articles deal with twentieth-century writings and authors. Initially, as guest editor, I intended to publish articles on earlier periods as well, since, as Louis Rubin and others have shown, the earlier literature
contributes in concrete and fascinating ways to the development of the literary imagination and intelligence that would flower in the twentieth-century Southern Literary Renascence and later.